Collagen biosynthesis stimulation and anti-melanogenesis of bambara groundnut (Vigna subterranea) extracts - Romchat Chutoprapat; Waraporn Malilas; Rattikarl Rakkaew; Sarinporn Udompong; Korawinwich Boonpisuttinant (Taylor & Francis Group, 2020)
Context Bambara groundnut (BG), originally from Africa, is widely distributed in Asian countries, especially in southern Thailand, and is used for food and functional foods. There is no report on the use of BG for ethnomedicine or cosmetics. Objective To investigate collagen biosynthesis stimulation and anti-melanogenesis of the BG extracts. Materials and methods The hulls (H) and seeds (S) of BG were collected from Trang province, Thailand and extracted by Soxhlet (S) and maceration (M) using ethanol, and boiled with distilled-water (B). Total phenolic (TPC) and total flavonoid (TFC) contents were quantified. The three antioxidant and tyrosinase inhibition activities were determined by DPPH, FIC and FTC; and the modified dopachrome methods, respectively. The collagen biosynthesis and the anti-melanogenesis activities were investigated by Sirius-Red and the melanin content assay. Results The yields of BG extracts ranged from 1.72% to 9.06%. The BG-SS extract gave the highest TPC and TFC. The BG-HM extract showed the highest antioxidant activities (SC50 of 0.87 ± 0.02 mg/mL, MC50 of 1.83 ± 0.09 mg/mL and LC50 of 0.70 ± 0.06 mg/mL), tyrosinase inhibition activity (IC50 of 0.45 ± 0.23 mg/mL), and anti-melanogenesis activities (72.9 ± 0.08%), whereas the BG-SB extract exhibited the highest stimulation of collagen biosynthesis (18.04 ± 0.03%). All BG extracts at 0.1 mg/mL showed no cytotoxicity on human dermal fibroblasts. Discussion The biological activities of BG extracts might be from their phytochemicals, especially phenolic and flavonoid contents. Conclusion The BG-HB and BG-HM extracts might be promising novel active sources for anti-aging and whitening cosmeceuticals.